2019
DOI: 10.1007/s13524-019-00808-z
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Parental Death in Childhood on Sons’ and Daughters’ Status Attainment in Young Adulthood in the Netherlands, 1850–1952

Abstract: Previous research on the impact of parental loss on labor market outcomes in adulthood has often suffered from low sample sizes. To generate further insights into the long-term consequences of parental death, I use the Historical Sample of the Netherlands (HSN). The HSN contains occupational information on life courses of a sample of more than 8,000 males and almost 7,000 females born between 1850 and 1922, a period of important labor market transformations. Roughly 20 % of the sample population experienced pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
12
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 62 publications
(80 reference statements)
0
12
1
Order By: Relevance
“…Previous authors have established this age as the most relevant for assessing the effect of early parental death (≤16 years) on the health of the elderly. 11,15,19,34 Sociodemographic data. The following data were recorded: age (<65/≥65 years), gender (male/female), marital status (married, widowed, separated-divorced, or never married), mean years of schooling (<11/≥11 years), economic difficulties (yes/no) and income in percentiles (≤50/>50).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous authors have established this age as the most relevant for assessing the effect of early parental death (≤16 years) on the health of the elderly. 11,15,19,34 Sociodemographic data. The following data were recorded: age (<65/≥65 years), gender (male/female), marital status (married, widowed, separated-divorced, or never married), mean years of schooling (<11/≥11 years), economic difficulties (yes/no) and income in percentiles (≤50/>50).…”
Section: Methodsmentioning
confidence: 99%
“…The analysis of the risk of dementia focused on the period of early parental death, that is, when the participants were aged ≤16 years. Previous authors have established this age as the most relevant for assessing the effect of early parental death (≤16 years) on the health of the elderly 11,15,19,34 …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In a recent meta‐analysis of case‐control studies, Simbi et al 12 reported that those experiencing parental death in childhood or adolescence were 1.76 times more likely to suffer from depression in later adult life, than controls. Beyond health, the impact of the death of a parent can result in lower self‐esteem, poorer educational outcomes and an increased likelihood to become involved in violent criminal behaviour 8,13 …”
Section: Introductionmentioning
confidence: 99%
“…However, because offspring are less dependent on mothers during this phase of life, the effects of maternal loss after weaning can be sub-lethal (9,16,22). If an offspring that is weaned (but still partially dependent on its mother) survives its mother's death, the offspring may experience long-lasting negative effects, including adverse behavioral or social outcomes in adolescence or adulthood (humans: (23,24); non-humans: (19,20,(25)(26)(27)(28)(29)(30)(31)). In baboons, chimpanzees, and elephants, motherless offspring may experience reduced survival during adolescence and adulthood, well after the maternal loss occurs, presumably because maternal loss results in a chronic reduction in body condition (13,21,26,32) (Figure 1, red arrow).…”
mentioning
confidence: 99%